1985
DOI: 10.1002/pd.1970050303
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone levels in midtrimester maternal and fetal plasma and amniotic fluid

Abstract: Testosterone was measured in maternal plasma (58 samples), amniotic fluid (71 samples) and fetal plasma (55 samples) in 79 patients between 15 and 23 weeks' gestation. Maternal plasma testosterone levels were unrelated to fetal sex. Amniotic fluid testosterone was significantly higher in male than female fetuses but did not reliably predict fetal sex. A correct diagnosis of fetal sex was made by testosterone assay of pure fetal plasma in 39 out of 40 males and in 15 out of 15 females using 1.70 nmol/l as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 17 publications
(16 reference statements)
3
62
1
Order By: Relevance
“…It seems therefore likely that the maternal compartment of the maternal-fetal unit is a fairly different one than the fetal compartment (i.e., the amnion sac). It has been shown rather convincingly in several studies (e.g., Nagamani et al, 1979;Rodeck et al, 1985;van de Beek et al, 2004) that amniotic fluid T levels are higher when measured in the presence of a male fetus compared to a female fetus. This supports the notion that prenatal exposure to T in fetuses is not so much via the more indirect maternal-fetal route as the fetal hormone transfer notion suggests, but rather via the other route, that is, the feto-fetal route.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It seems therefore likely that the maternal compartment of the maternal-fetal unit is a fairly different one than the fetal compartment (i.e., the amnion sac). It has been shown rather convincingly in several studies (e.g., Nagamani et al, 1979;Rodeck et al, 1985;van de Beek et al, 2004) that amniotic fluid T levels are higher when measured in the presence of a male fetus compared to a female fetus. This supports the notion that prenatal exposure to T in fetuses is not so much via the more indirect maternal-fetal route as the fetal hormone transfer notion suggests, but rather via the other route, that is, the feto-fetal route.…”
Section: Discussionmentioning
confidence: 97%
“…In singleton pregnancies, differences in maternal serum levels of androgens have been found in women pregnant with males and women pregnant with females (e.g., Meulenberg & Hofman, 1991). There are also studies, however, which have failed to find such a relationship between fetal sex and maternal serum steroid levels (e.g., Nagamani et al, 1979;Rodeck et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is done during the second trimester of pregnancy, during a relatively narrow time window (usually 14-20 weeks of gestation) which fortunately coincides with the serum testosterone peak period in male fetuses. This peak is also apparent in amniotic fluid: several studies have documented a large sex difference in amniotic androgens [132,141,145,147,[163][164][165]. It is interesting to note that amniotic fluid was used to index fetal hormonal levels well before it was recognized as an opportunity by behavioral scientists [147].…”
Section: Interpretation Of Findings: Amniotic Hormones and Behaviormentioning
confidence: 99%
“…Given the risk of obtaining blood from the fetus, there are very limited data directly comparing testosterone in amniotic fluid to that from fetal blood. One study at 15-23 weeks of gestation [165] reported no significant correlations among testosterone levels obtained from fetal plasma and amniotic fluid, but it is unclear whether there would be significant associations if assessments were done earlier in development or if multiple measures were used. Androgens in amniotic fluid are also unrelated to androgens measured in maternal blood in the same period, as shown in studies in early-and midgestation [145,165].…”
Section: Interpretation Of Findings: Amniotic Hormones and Behaviormentioning
confidence: 99%